The effect of low dose midazolam in addition to ondansetron on post-operative nausea and vomiting in laparoscopic cholecystectomy a comparative study (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Nausea, retching and vomiting are among the most common postoperative complaints. Premedication with low dose midazolam in addition to ondansetron is more effective in controlling postoperative nausea and vomiting. Objectives This study was designed to observe the effect of low dose midazolam 7.5mg in addition to ondansetron 4mg on postoperative nausea and vomiting in laparoscopic cholecystectomy. Methods 100 patients of ASA grade I and II, age range 30-50 years and weight 50-70 kg were randomly selected by a blind envelop method. They were equally divided into four groups of 25 patients in group each. Group I received vitamin, Group II ondansetron 8mg, Group III ondansetron 8mg and midazolam 7.5mg and Group IV ondansetron 4mg and midazolam 7.5 mg orally one hour before operation. In the recovery room occurrence of nausea and vomiting was assessed for 24 hours. Results The incidence of nausea was in vitamin Group I 64%, in ond8 group II 32%, in ond8+mid7.5 group III 24% and in ond4+mid7.5 group IV 24%. The incidence among the groups was highly significant (p=0.008). The incidence of vomiting was in vitamin Group I 16%, in ond8 group II 16%, in ond8+mid7.5 group III 8% and in ond4+mid7.5 group IV 8%. The difference among the groups were not significant (p=0.808). Conclusion Low dose midazolam 7.5mg in addition to ondansetron 4mg is more effective in controlling postoperative nausea and vomiting in laparoscopic cholecystectomy. DOI: http://dx.doi.org/10.3329/jbsa.v24i1.19793 Journal of Bangladesh Society of Anaesthesiologists 2011; 24(1): 8-12